Intelligent agent for electronic commerce / Lai Siew Cheng - Lai , Siew Cheng (2001)
The objective of this project is to develop a system that can assists a user to make decision in online transactions for residential houses. In order to achieve this objective, an intelligent agent will be built where it will help the user to find relevant information of the houses based on they requirement. Furthermore, a prediction tool will also be developed to predict the price of the required house on the market. Artificial neural network will be used here, where the LVQ network is used to build the system. The neural network will be implemented in the filtering module and the prediction module of the system. Matlab has been chosen as the software to develop the network since it contained the neural network toolbox and the database toolbox to import and export data to the Matlab environment. After implementation, the system is supposed to perform two tasks and that are to provide user with relevant information of the required house and the predicted price of the house in the current market. The system has been built, and the implementation processes where, how the neural network and the interfaces are developed arc described in details. After that. the system is evaluated to ensure that it has met the goal set earlier. Here, the system strengths and limitations will be discussed. Finally, a conclusion of the system on the whole is presented at the end of the report.